Bullying and students with disabilities strategies and techniques to create a safe learning environment for all - McNamara, Barry E. 1949- (Corwin, a SAGE Company, 2013)
"Drawing on extensive studies on bullying in schools, Barry Edwards McNamara provides a research-based overview to understand bullying. Additionally, this book shows how to identify bullies and victims and implement an effective and inclusive bullying prevention program"-- Back cover.